Communicating in small groups : - Beebe, Steven A. (Pearson, 2014)
Known for its wealth of practical, relevant, and up-to-date information, Communicating in Small Groups balances the principles of small group communication with real world applications. With an emphasis on real world examples, technology, and ethical collaboration, the 10th edition of Communicating in Small Groups: Principles and Practices helps students enhance their performance in groups and teams, while giving them insight in to why group and team members communicate as they do.